Ossifying fibromyxoid tumor: A rare case report with review of literature and its differential diagnosis - Karthik Dhandapani; Jahnavi Gandhi; Amisha Gami (Wolters Kluwer Medknow Publications, 2024)
Ossifying fibromyxoid tumor (OFMT) is a rare mesenchymal tumor of uncertain histogenesis with intermediate malignant potential presenting commonly in the fifth to sixth decade in the proximal limb and limb girdle. A 65-year-old male patient presented with a slow-growing gluteal mass. Wide local excision performed showed a well-defined tumor in the subcutaneous plane with a partially hard outer shell. Microscopy showed a moderately cellular tumor having cords and nests of round to ovoid cells with moderate cytoplasm and bland nuclei embedded in a myxo-hyaline matrix. An incomplete peripheral rim of ossification was seen. Pleomorphism/high cellularity was not seen. Mitosis was <2/50 high-power field. On immunohistochemistry, both S100 and desmin were positive. A diagnosis of typical OFMT was rendered. Even though rare with many morphological mimics, OFMT should be diagnosed with precision as most of these tumors are low-grade tumors that require only wide local excision and close follow-up without any adjuvant therapy.